MOBILE AND DISTANCE EDUCATION IN TURKISH EDUCATION SYSTEM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Mobile education: This is an educational process in which students use the opportunities provided by mobile technologies. Mobile technologies were created as a means of communication, entertainment and networking, but under the influence of teachers, they began to be used as an educational tool. Mobile learning has the characteristics of social interaction, individualization, portability, networking, and context sensitivity.